Clinical and genetic characterization of children with cubilin variants - GÖKCE, İBRAHİM; ATA, PINAR; ALPAY, HARİKA; GÜVEN, SERÇİN; ALAVANDA, CEREN; ÇİÇEK DENİZ, NESLİHAN; PUL, SERİM; DEMİRCİ BODUR, ECE; YILDIZ, NURDAN (My University, 2022)
Background Cubilin is one of the receptor proteins responsible for reabsorption of albumin in proximal tubules and is encoded by the CUBN gene. We aimed to evaluate clinical and genetic characterization of six patients with proteinuria who had CUBN mutations. Methods Patients’ characteristics, serum creatinine, albumin, vitamin B12 levels, urine analysis, spot urine protein/creatinine, microalbumin/creatinine, beta-2 microglobulin/creatinine ratios, estimated glomerular fltration rates (eGFR), treatments, kidney biopsies, and genetic analyses were evaluated. Results Six patients (2 female, 4 male) with an incidental finding of proteinuria were evaluated. Mean admission age and follow-up time were 7.3 ± 2.9 and 6.5 ± 5.6 years, respectively. Serum albumin, creatinine, and eGFR were normal; urine analysis revealed no hematuria, and C3, C4, ANA, and anti-DNA were negative; kidney ultrasonography was normal for all patients. Urine protein/creatinine was 0.9± 0.3 mg/mg, and microalbumin was high in all patients. Serum vitamin B12 was low in two patients and normal in four. Kidney biopsy was performed in four patients, three demonstrated normal light microscopy, and there was one focal segmental glomerulosclerosis (FSGS). Genetic tests revealed four homozygous and two compound heterozygous mutations in the C-terminal part of cubilin. All patients had normal eGFR and still had non-nephrotic range proteinuria at last visit. Conclusions CUBN gene mutations should be considered in patients with isolated non-nephrotic range proteinuria and normal kidney function. Diagnosing these patients, who are thought to have a better prognosis, is important in terms of avoiding unnecessary treatment and predicting prognosis. CUBN gene mutations may also present as FSGS which extends the spectrum of renal manifestation of these patients.
Keywords: Children; Focal segmental glomerulosclerosis; Proteinuria